Can Platelet-Rich Plasma Enhance Anterior Cruciate Ligament and Meniscal Repair? - Hutchinson, Ian D.; Rodeo, Scott A.; Perrone, Gabriel S.; Murray, Martha M. (The Journal of Knee Surgery, 2015)
The use of platelet-rich plasma (PRP) to improve clinical outcome following a soft tissue injury, regeneration, and repair has been the subject of intense investigation and discussion. This article endeavors to relate clinical and basic science strategies focused on biological augmentation of the healing response in anterior cruciate ligament (ACL) and meniscus repair and replacement using PRP. Therein, a translational feedback loop is created in the literature and targeted towards the entire multidisciplinary team. Ultimately, it is hoped that the theoretical benefits of PRP on soft-tissue interfacial healing will emerge clinically following a careful, focused characterization at the benchtop, and prospective randomized controlled clinical study.
Keywords: ACL; meniscus; PRP; biologics; meniscal repair; ACL reconstruction